2015
DOI: 10.1021/ct500864r
|View full text |Cite
|
Sign up to set email alerts
|

Combined Covalent-Electrostatic Model of Hydrogen Bonding Improves Structure Prediction with Rosetta

Abstract: Interactions between polar atoms are challenging to model because at very short ranges they form hydrogen bonds (H-bonds) that are partially covalent in character and exhibit strong orientation preferences; at longer ranges the orientation preferences are lost, but significant electrostatic interactions between charged and partially charged atoms remain. To simultaneously model these two types of behavior, we refined an orientation dependent model of hydrogen bonds [Kortemme et al. 2003] used by the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
301
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(302 citation statements)
references
References 76 publications
1
301
0
Order By: Relevance
“…Mutations were defined as improving helical propensity if they were in helical regions and if Rosetta energy calculations showed ΔΔG calc of less than −0.15 Rosetta energy units for the energy term that accounts for the compatibility of the amino acid identity with the local backbone ϕ and ψ dihedral angles (p_aa_pp). Positions were defined as buried if they had >21 and >75 neighboring nonhydrogen atoms within 10 and 12 Å, respectively, according to the Rosetta Features Reporter (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…Mutations were defined as improving helical propensity if they were in helical regions and if Rosetta energy calculations showed ΔΔG calc of less than −0.15 Rosetta energy units for the energy term that accounts for the compatibility of the amino acid identity with the local backbone ϕ and ψ dihedral angles (p_aa_pp). Positions were defined as buried if they had >21 and >75 neighboring nonhydrogen atoms within 10 and 12 Å, respectively, according to the Rosetta Features Reporter (31,32).…”
Section: Methodsmentioning
confidence: 99%
“…This raises the question of how best we should define and measure NCIs, and, of course, how do we model and assess them computationally and quantitatively. For example, recent work on the Rosetta forcefield has demonstrated that simultaneously modeling the electrostatic and covalent properties of hydrogen bonds improves protein-structure prediction, 47 and work on polarizeable, multipolar forcefields such as AMOEBA 48 has challenged the notion of linear hydrogen bonding in a-helices. Further quantification of the contributions from each NCI and how they cooperate should inform the development of more-accurate forcefields for molecular modeling and mechanics, and thus afford a deeper understanding of protein structure and stability.…”
Section: Discussionmentioning
confidence: 99%
“…The talaris2013 scoring function was used for Rosetta (65). For the combined Rosetta-TERMs design procedure, we limited the amino acids that Rosetta could use at position r to the smallest set that accounted for at least 80% cumulative probability according to TERM-based self-energy (i.e., fa 1 , .…”
Section: Methodsmentioning
confidence: 99%
“…To this end, we asked whether TERM statistics would predict sequences optimally compatible with native backbones to be close to the corresponding native sequences. This experiment, known as "native sequence recovery," is a common means of evaluating scoring functions in computational protein design (65).…”
Section: A Small Number Of Terms Describe Most Of the Structural Univmentioning
confidence: 99%